(untitled) (American Journal of Islam and Society, 1985)
Nigeria is the most populous state in Africa south of the Sahara. Her geography and her history together make her an interesting sociopolitical and cultural experiment. It is a land with believers in both Islam and Christianity. A country whose northern parts were the prizes of jihadic victory of a highly Islamized Fulani elite, and whose southern portions are inhabited by peoples who were voluntarily or involuntarily brought under the control of the marching Christian soldiers determined to expand the domain of imperial Europe and committed to recruiting souls for Jesus. Nigeria is a meeting ground for two periods in African history. It is the place where Islam still rejoices over its past glories and successes; it is also a place where Euro-Western Christianity has made a major breakthrough. It is against this background, and with such facts in mind, that the subject of Nigerian-Arab relations is here explored. I divide this paper into four parts. The first part is a brief historical sketch of the impact of Arabs and Islam on the Nigerian society and the Nigerian mind. The second part addresses itself to the early post-colonial period in NigerianArab relations; the third part discusses Nigerian-Arab relations under military rule in Nigeria; the fourth part discusses Nigeria’s Third Republic and the Arab states. A. Islam, Arabs and Nigeria The arrival of Islam in northern Nigeria dates back to the 11th century and constitutes a major development in the history of this region of Africa. It not only linked the Hausas, the Fulanis, and other Islamized ethnic groups with the wider world of Islam to the north, northeast, and west, but it also opened up the possibility of Muslim expansion southwards. Indeed, one of the effects of lslamization in Northern Nigeria was the emergence of a full-fledged Islamic culture and civilization in certain parts of what we now call Nigeria. The sphere of ...